Distinct Evolutionary Patterns of NBS-Encoding Genes in Three Soapberry Family (Sapindaceae) Species - Zhou, Guang-Can; Li, Wen; Zhang, Yan-Mei; Liu, Yang; Zhang, Ming; Meng, Guo-Qing; Li, Min; Wang, Yi-Lei (Frontiers in Genetics, 2020)
Nucleotide-binding site (NBS)-type disease resistance genes (R genes) play key roles in plant immune responses and have co-evolved with pathogens over the course of plant lifecycles. Comparative genomic studies tracing the dynamic evolution of NBS-encoding genes have been conducted using many important plant lineages. However, studies on Sapindaceae species have not been performed. In this study, a discrepant number of NBS-encoding genes were identified in the genomes of Xanthoceras sorbifolium (180), Dinnocarpus longan (568), and Acer yangbiense (252). These genes were unevenly distributed and usually clustered as tandem arrays on chromosomes, with few existed as singletons. The phylogenetic analysis revealed that NBS-encoding genes formed three monophyletic clades, RPW8-NBS-LRR (RNL), TIR-NBS-LRR (TNL), and CC-NBS-LRR (CNL), which were distinguished by amino acid motifs. The NBS-encoding genes of the X. sorbifolium, D. longan, and A. yangbiense genomes were derived from 181 ancestral genes (three RNL, 23 TNL, and 155 CNL), which exhibited dynamic and distinct evolutionary patterns due to independent gene duplication/loss events. Specifically, X. sorbifolium exhibited a “first expansion and then contraction” evolutionary pattern, while A. yangbiense and D. longan exhibited a “first expansion followed by contraction and further expansion” evolutionary pattern. However, further expansion in D. longan was stronger than in A. yangbiense after divergence, suggesting that D. longan gained more genes in response to various pathogens. Additionally, the ancient and recent expansion of CNL genes generated the dominance of this subclass in terms of gene numbers, while the low copy number status of RNL genes was attributed to their conserved functions.